Advancing paediatric cardiac imaging: a comprehensive analysis of the feasibility and accuracy of a novel 3D paediatric transoesophageal probe - Karsenty, Clément; Hadeed, Khaled; Pyra, Pierrick; Guitarte, Aitor; Djeddai, Camelia; Vincent, Remi; Dulac, Yves; Silagdze, Ia; Gobin, Julie; Combes, Nicolas; Ratsimandresy, Miarisoa; Berthomieu, Lionel; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims Pediatric transoesophageal echocardiography (TOE) probes have remained two-dimensional (2D) limiting their use compared to adults. While critical in pediatrics for interventions and post-surgery assessments, technological advancements introduced a three-dimensional (3D) pediatric TOE probe. This study assessed the new 3D pediatric TOE probe (GE 9VT-D) for feasibility, handling, and imaging quality. Methods and results At Children's Hospital of Toulouse, 2-month prospective study enrolled children undergoing TOE with the new probe. All imaging modalities were rated by 2 operators using a 5-point Likert-type scale from 1 (very poor) to 5 (very good) quality. Forty-five children, median age 3.7 (range: 2 months-14.7 years) median weight 7.8kg (range: 4.3-48 kg) underwent 60 TOEs: 25% pre-surgery, 45% post-surgery, 28% during percutaneous procedures, and 2% in intensive care. Probe handling was 'very easy' in all cases without adverse events. The median score of 2D, 2D colour, pulsed Doppler and 3D were noted 5 out of 5 and continuous Doppler and 3D colour 4 out of 5. The 3D image quality remained consistent irrespective of the patient weighing above or below 7.8 kg (p=0.72). Postoperative TOEs identified two cases needing further interventions, emphasizing its value in evaluating surgical outcomes and also for guiding percutaneous interventions. Conclusion Our comprehensive evaluation demonstrates that the new 3D pediatric TOE probe is feasible and provides high-quality imaging in pediatric patients. The successful integration of this novel probe into clinical practice has the potential to enhance diagnostic accuracy and procedural planning, ultimately optimizing patient outcomes in pediatric cardiac care.